Reconsidering earthquake scaling - J. Gomberg; A. Wech; K. Creager; K. Obara; D. Agnew (Geophysical Research Letters)
Abstract The relationship (scaling) between scalar moment, M0, and duration, T, potentially provides key constraints on the physics governing fault slip. The prevailing interpretation of M0‐T observations proposes different scaling for fast (earthquakes) and slow (mostly aseismic) slip populations and thus fundamentally different driving mechanisms. We show that a single model of slip events within bounded slip zones may explain nearly all fast and slow slip M0‐T observations, and both slip populations have a change in scaling, where the slip area growth changes from 2‐D when too small to sense the boundaries to 1‐D when large enough to be bounded. We present new fast and slow slip M0‐T observations that sample the change in scaling in each population, which are consistent with our interpretation. We suggest that a continuous but bimodal distribution of slip modes exists and M0‐T observations alone may not imply a fundamental difference between fast and slow slip.